The impact of credit shocks on the European labour market - Katalin Bodnár; Ludmila Fadejeva; Marco Hoeberichts; Mario Izquierdo; Christophe Jadeau; Eliana Viviano (Baltic Journal of Economics, 2021)
The sovereign debt crisis led to financial difficulties for European firms and a decline in the use of labour input. We use qualitative firm-level data for 24 European countries, collected within the third wave of the Wage Dynamics Network (WDN3) of the ESCB, to propose a cross-country analysis of the relationship between a credit shock and labour markets. We first derive a set of indices measuring difficulties in accessing the credit market for the period 2010-2013. Second, we provide a description of the relationship between credit difficulties and changes in labour input, both along the extensive and the intensive margins as well as on wages. We find strong and significant correlation between credit difficulties and adjustments along both the extensive and the intensive margin. In the presence of credit market difficulties, firms also cut wages by reducing the variable part of wages. This evidence suggests that credit shocks can affect not only the real economy, but also nominal variables.
Keywords: D53; E24; E44; G31; G32; 330; Credit difficulties; intensive margin; labour input adjustment; survey data; wage adjustment